Progestin-primed ovarian stimulation versus GnRH antagonist protocol in poor responders: Risk of premature LH surge and outcome of oocyte retrieval - Tzu-Ching Kao; Yun-Chiao Hsieh; Ih-Jane Yang; Ming-Yih Wu; Mei-Jou Chen; Jehn-Hsiahn Yang; Shee-Uan Chen (Journal of the Formosan Medical Association, 2023)
Purpose: For poor ovarian responders (PORs), gonadotropin-releasing hormone (GnRH) antagonist was commonly used for prevention of premature LH surge during controlled ovarian stimulation (COS) over the past two decades. The application of progestin-primed ovarian stimulation (PPOS) recently increased, but the role of PPOS for PORs was uncertain. We aimed to analyze the incidence of premature luteinizing hormone (LH) surge and the outcome of oocyte retrieval among PPOS and GnRH antagonist protocol for PORs. Methods: This was a single-center retrospective study, which enrolled the PORs (defined by the Bologna criteria) undergoing COS with PPOS or flexible GnRH antagonist protocol during January 2018 to December 2021. We compared the incidence of premature LH surge (LH > 10 mIU/mL) and the outcome of oocyte retrieval between the PPOS group and the GnRH antagonist group. Results: A total of 314 women were recruited, with 54 in the PPOS group and 260 in the GnRH antagonist group. The PPOS group had lower incidence of premature LH surges compared with the GnRH antagonist protocol group (5.6% vs 16.9%, P value 0.035). There was no significant difference between the two groups regarding the number of oocytes retrieved (3.4 vs 3.8, P value 0.066) and oocyte retrieval rates (88.9% vs 88.0%, P value 0.711). Conclusion: Compared with PPOS, GnRH antagonist protocol had higher risk of premature LH surges for PORs but may not affect pregnancy rates. PPOS is suitable for oocyte or embryo cryopreservation, but should not totally replace GnRH antagonist protocol for patients undergoing in vitro fertilization (IVF).